The adventure of English [videorecording (DVD)] : the life story of a remarkable language - Bee, Robert; Thomas, David; Wattis, Nigel; Bragg, Melvyn, 1939- (Athena, 2009)
Melvyn Bragg and other experts explore the 1,500-year history of the English language and answer questions such as: How did it grow from a relatively insignificant Germanic dialect to become the premier language of culture, commerce, and diplomacy around the globe? Includes guide for group discussions, avenues for further learning, biographies, web extras, and much more.